The Effect of the Application of the Model Problem Based Learning on Critical Thinking Ability in Social Science Lessons in Class IV of Elementary 2 Pesanggrahan - Setiawan, Ade; Syaodih , Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The purpose of this study was to describe the effect of Problem Based Learning (PBL) learning on Students' Critical Thinking Ability between classes that apply the Problem Based Learning model and those that apply conventional models. The research design used was Quasy Experimental Research. This research will be conducted at SD Negeri 2 Pasanggrahan with the sample used, namely class IV consisting of 2 study groups or a class of 40 students. Data collection methods used were tests and observations. The data analysis technique used the t test to determine differences in critical thinking skills in the experimental class after being given treatment. The results of data analysis using the t test obtained results -t count <-t table (-3.426 <-1.997) and a significance value <0.05 (0.001 <0.05). Therefore, it shows that there is a significant difference in students' critical thinking skills between the experimental class and the class using the conventional model.